Quantifying the influence of urban road surface roughness on heavy metals pollution in road-deposited sediment's accumulation and wash-off - Faisal, Muhammad (Water science and technology : a journal of the International Association on Water Pollution Research, 2023)
Surface roughness is an important factor to consider when evaluating the loads of surface runoff caused by road-deposited sediment (RDS) wash-off and creating management solutions for this occurrence in metropolitan areas. Nevertheless, the implications of surface roughness on RDS development and escape remain unclear due to a paucity of experimental evidence distinguishing the significance of surface roughness. This research aimed to differentiate the impact of surface roughness on RDS accumulation and wash-off by employing paired asphalt, rainfall simulation designs, and concrete road surfaces. Our findings indicated that normal asphalt surfaces are typically rougher than typical concrete surfaces because they frequently contain deeper depressions. Compared to concrete surfaces, asphalt surfaces typically retain more RDS, a higher proportion of coarse aggregates, more RDS wash-off loads, and a lower proportion of wash-off. Surface roughness has varying impacts on the RDS motilities of particulates of varying sizes during rainy runoff; nevertheless, the settleable particles (40-150 μm) were more noticeably impacted by it. The first flush effect also seemed to be more pronounced on surfaces with lower roughness. Hence, surface roughness has a significant impact on how RDS builds on and is washed off of various road aspects